Behavior, stress and metabolism of a parthenogenic lizard in response to flyover noise - Kepas, Megen E.; Sermersheim, Layne O.; Hudson, Spencer B.; Lehmicke, Anna Joy J.; French, Susannah S.; Aubry, Lise M. (Frontiers in Amphibian and Reptile Science, 2023)
The Colorado checkered whiptail (Aspidoscelis neotesselatus) is a parthenogenetic lizard that is listed as a “species of special concern” in the state of Colorado. A. neotesselatus occupies a small range that includes the US Army Fort Carson Military Base in Colorado Springs, Colorado. The species is exposed to a variety of military disturbances, including aircraft flyover noise. We sampled 82 females during the 2021 reproductive season to assess whether scheduled flyovers would impact the behavior, stress, and metabolism of A. neotesselatus, while controlling for size and reproductive stage differences. We measured corticosterone (CORT) as a marker of anthropogenically induced stress during flyovers compared to a control. We further tested for the downstream effects of flyovers on plasma glucose (free energy available to tissues), elevated metabolism with oxidative stress (ROMs), and ketone bodies (alternative cerebral energy substrates to glucose). When disturbed by flyovers, these lizards spent less time moving but more time eating. Aircraft noise also increased CORT when controlling for clutch size, indicating a stress response driven by flyovers, as well as an independent effect of reproductive investment on CORT. CORT did not affect plasma glucose. Flyovers led to a marginally decrease in circulating ROMs, with gravid females experiencing lower plasma ROMs than non-gravid females, but that later effect was independent of flyovers. Flyovers significantly increased ketone bodies, with smaller animals experiencing higher ketone concentrations than larger individuals, yet the effect of size on ketone bodies was independent of the flyover treatment. Although A. neotesselatus seem to adjust their behavior and eat more to buffer the potentially negative effect of flyovers on energetic pathways, they still appear to suffer a metabolic cost driven by the stress response via ketone accumulation, as well as a reproductive cost driven by clutch size investment that is independent of flyover disturbance. We suggest that military aircraft operators attempt to avoid dense populations of A. neotesselatus during the reproductive season or fly at altitudes that lead to decibel reads that fall below 50 dB at ground level, as a cautious management step that ensures the resilience and local abundance of A. neotesselatus at Fort Carson.